Three Motions based on Mullā Sadrā's Three Philosophical Journeys: Natural Motion, Substantive Motion, Renewal of Likes - Ali Babaei; Seyed Mokhtar Mousavi (Journal of Philosophical Investigations, 2022)
It is recognized by scholars that Mullā Sadrā has three philosophical journeys: Fundamentality of quiddity, Fundamentality of existence on gradational unite, and Fundamentality of existence on individual Unite; With this in mind, the issue of motion, an important issue in Sadra's wisdom, has changed as a result of these three journeys; In this regard, the belief of “Natural Motion” is commensurate with the first level, the belief of “Substantial Motion” is appropriate with the second level, and the belief of “Renewal of Likes” is commensurate with the third philosophical journey of Mullā Sadrā; Each of this three journeys has its requirements and causes the evolution of related issues. Addressing the above-mentioned issues, we have implicitly emphasized the longitudinal relationship between natural motion, substantial motion, and the renewal of the like, and their adherence to the longitudinal journey of Sadrā's wisdom.